Fenomena Revenge Tourism Pada Industri MICE Di Indonesia Studi Kasus Pada Exhibition Event di Indonesia - Didit Siswodwiatmoko; Kurniawan Gilang (Bisnis Event, 2023)
The phenomenon of revenge tourism pertains to the inclination of individuals to embark on travels as a way of "getting even" after having been constrained for a prolonged period because of the COVID-19 pandemic. This has led to the implementation of policies by governments, such as Indonesia and other nations worldwide, that restrict human movement during the COVID-19 pandemic. The bans on activities outside the home and travel in Indonesia have led to the emergence of anxiety, boredom, stress, and prolonged fatigue among many people. The MICE industry is experiencing rapid growth within the tourism sector. This is due to the high demand for individuals and companies to hold meetings and events. However, the current mobility restriction policy has led to the cancellation of certain MICE activities due to the risk of large gatherings. Nonetheless, the exhibition and conference business sector has been able to adapt to the current situation by optimizing IT technology, events that were initially held offline when the pandemic spread turned into online events. As a result, the conference and exhibition sector demonstrates greater resilience in comparison to other industries like impresarios and incentive trips. The nature of this research is descriptive and qualitative, utilizing a phenomenological approach to delve deeper into the phenomenon of revenge tourism. The focus will be on the perspectives of the organizers and exhibitors of such events, with the aim of drawing conclusions about the extent of this phenomenon in specific fields.